Polyextremotolerant black fungi: oligotrophism, adaptive potential, and a link to lichen symbioses - Gostinčar, Cene; Muggia, Lucia; Grube, Martin (Frontiers in Microbiology, 2012)
Black meristematic fungi can survive high doses of radiation and are resistant to desiccation. These adaptations help them to colonize harsh oligotrophic habitats, e.g. on the surface and subsurface of rocks. One of their most characteristic stress-resistance mechanisms is the accumulation of melanin in the cell walls. This, production of other protective molecules and a plastic morphology further contribute to ecological flexibility of black fungi. Increased growth rates of some species after exposure to ionizing radiation even suggest yet unknown mechanisms of energy production. Other unusual metabolic strategies may include harvesting UV or visible light or gaining energy by forming facultative lichen-like associations with algae or cyanobacteria. The latter is not entirely surprising, since certain black fungal lineages are phylogenetically related to clades of lichen-forming fungi. Similar to black fungi, lichen-forming fungi are adapted to growth on exposed surfaces with low availability of nutrients. They also efficiently use protective molecules to tolerate frequent periods of extreme stress. Traits shared by both groups of fungi may have been important in facilitating the evolution and radiation of lichen-symbioses.